ENERGY EXTRACTION EFFICIENCY OF IN-STREAM MULTISTAGE MICRO-HYDRO TURBINE - M. Shahidul, Islam; Syed Tarmizi, Syed Shazali; Sarip, A.S.H. (2017)
This paper describes the techniques for estimating thekinetic energy extraction efficiency of a multistage micro-hydro turbinewith five blades. The broad objective of this study was to measure the overall energy extraction efficiency of the said turbine system. Thisexperiment was conducted in a closed-loop water channel,and the velocity range was from 0.5 m/sto 1.1 m/s. The estimated overall energy efficiency of this turbine ranged from 12.8 percent to 25 percent. However, the most energy-inefficient component hereappeared to be the turbine’s blades, whose valuewas 84 percent. Indeed, energy inefficiency oftheblades contributed to a reduction inthe overall energy efficiency. This study concludes that in-stream multistage micro-hydro turbinesarea useful mechanical device for generating low-cost green energy from water. However, theenergy extraction efficiency of micro-hydro turbinesdepend on the interaction between the turbine blades and water flux; these two variables can bemanipulatedto increasetheenergy extraction efficiency. The goals forfuture studiesaretofindoutthe causes of energy extraction inefficiency andto increase the efficiency so that suchturbines can becomeeconomically sustainable.